Work Ethics in Saudi Arabia: The Critical Role of Women and Expatriates - Ali, Abbas J.; Al-Aali, Lamya; Krishnan, Krish S. (Journal of promotion management, 2024)
The attitude of Saudis and expatriate managers toward work has taken on added value in recent years. This has come about as the Kingdom of Saudi Arabia has embarked on profound and ambitious economic and social changes outlined in Vision 2030. Managers are instrumental in successfully executing these strategic moves. However, managers face intense and immediate challenges when publicly voicing their concerns. This study was undertaken to shed light on the nature of work ethics and work involvement in the Kingdom. The research subjects were men and women managers and encompassed both citizens and expatriates. We found differences in the attitudes of men and women and between citizens and expatriates. The results were viewed in the sociopolitical context, and issues related to work ethics and to the role of women and expatriates were delineated. Business and social implications for policymakers and multinational corporations were provided.